SUNDANESE AHMADIYYAâ€™S PUPUJIAN OF THE MAHDI IN WEST JAVA - Rohmana, Jajang A (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This article focuses on the local tradition of Ahmadiyya in West Java in the form of Sundanese oral literature entitled Pupujian Imam Mahdi, the song of praise of the Mahdi. It is not only related to strengthening the so-called â€œSundanese Ahmadiyyaâ€ identity through cultural acculturation, but also an important channel in their acceptances in regions with the largest adherents in Indonesia. Through literary and cultural identity analysis, I argue that the literary and cultural channels contributed to the acceptance of minority groups in Indonesia. Through pupujian Imam Mahdi, for instance, Ahmadiyya teachings on the messianistic figure were acculturated into the Sundanese literary tradition. It becomes a frame of movement towards the formation of the Sundanese Ahmadiyah identity. The pupujian is used to support their existences through the same cultural representation as other Sundanese people. It is a cultural strategy carried out by the most controversial minority group among the rejection of the most groups. This study is also important in revealing Ahmadiyya's contribution to the Sundanese local culture which may not be recognized by others. It actually becomes a peculiarity of Ahmadiyya identity in the Indonesian archipelago which is different from other cultural representation of Ahmadiyya in various regions in the world.